The Dirty Dozen Scale: Validation of a Polish Version and Extension of the Nomological Net - Czarna, Anna Z.; Jonason, Peter K.; Dufner, Michael; Kossowska, Małgorzata (Frontiers in Psychology, 2016)
In five studies (total N = 1,300) we developed and validated a Polish version of the Dirty Dozen measure (DTDD-P) that measures the three traits of the Dark Triad, Machiavellianism, psychopathy, and narcissism. We detail the presence and stability of a bifactor structure of the 12 items and present evidence for good internal consistency and test–retest reliability. We examine the nomological network surrounding the Dark Triad and show that both the Dark Triad total score and the subscales have acceptable validity. We also present evidence on the Dark Triad and moral behavior. Dark Triad predicts utilitarian moral choice (e.g., approval for sacrificing somebody’s life for the sake of saving others) and this link is mediated by low empathic concern. In total, our results suggest that the Polish Dirty Dozen—Parszywa Dwunastka—is valid, stable, and useful for the study of lingering puzzles in the literature.